Mobile Money and Financial Inclusion of Rural Women in the Informal Sector: A Case of Users of Orange Money in Yagoua. - DJAOWE, Joseph; AKO TIKU, Leonel (Archives of Business Research, 2022)
The purpose of this article is to assess the influence of Mobile Money on the financial inclusion of rural women in the informal sector. Women's access to financial services is a key factor in economic growth and development. This work aims to measure the impact of mobile finance, mobile wallet and mobile payment on the financial inclusion of women. To this end, a questionnaire was administered to a sample of 98 rural women working in the informal sector. Data from the surveys were analyzed using SPSS software and subjected to the binary logistic regression test. From this investigation, the following results emerge: (1) mobile finance positively influences the financial education of rural women in the informal sector; (2) the mobile wallet contributes to an increase in the income of rural women in the informal sector and (3) mobile payment accelerates the access of rural women in the informal sector of Yagoua to financial services. In order to further promote the financial inclusion of rural women, moderately literate, formerly excluded from the traditional financial system and working in the informal sector of Yagoua, it would be wise to find ways and means to enable them to access the services of formal financial institutions through Mobile Money.